Renewing the Nous: Watchfulness and Praying - Hendi Hendi (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2020)
Abstract. This paper is a review of renewing and guarding the nous in the Philokalia teaching. The Philokalia is a collection of spiritual texts written between the fourth and fifteenth centuries by the monks of the Orthodox Christian tradition. Christian spirituality is very concrete and practical not mysterious or abstract. Its various aspects are described well in the Philokalia but the Philokalia remains relatively unknown while people seek to satisfy their thirst by consuming from the heresies teaching that ever existed from the beginning of time. One of the most important spiritual aspects that needs to be re-discovered today is renewing the intellect or nous. The fathers of Philokalia concern much on the renewing and guarding the nous. The way to renew the nous is only guarding the nous with all nepsis (prosoche) and praying (proseuche). They emphasized nepsis or watchfulness because the arch - enemy of the soul is a certain kind of thought which they described with the word logismoi. Nepsis and praying are the way to contend against the logismoi and the passions.